DETERMINATION OF MOST RELIABLE BONY STRUCTURE FOR AGEING OF CARASSIUS CARASSIUS (LINNE, 1758) INHABITING IN DUHOK RIVER (IRAQ) - MOHAMMED, JIHAD SALEEM (Fırat Üniveristesi, 2020)
Bu çalışmada, Duhok Nehri'nde yaşayan Carassius carassius (Linne, 1758) populasyonunda karşılaştırmalı yaş tayini yapılması amaçlanmıştır. Bu amaçla 71 balık örneği (57 erkek ve 14 dişi) elde edildi. Çalışma Fırat Üniversitesi Su Ürünleri Fakültesi balık anatomisi laboratuvarında gerçekleştirildi. Balık örneklerinin uzunluğu ve ağırlığı belirlendi. Yaş tayininde kullanılan omurlar, pullar, otolitler, ve operkulumlar çıkarılarak, temizlenmiş ve etiketlenmiştir. Daha sonra, kemik yapıları binoküler mikroskop altında incelendi. Her kemik yapısının yaş halkaları üç kez ve bir gün arayla sayıldı. Her kemik yapısı için belirlenen yaş grupları, bu gruplardaki bireylerin sayı ve yüzde dağılımları tablolarla, kemik yapısı arasındaki yaş eşleşmesi rakamlarla ifade edilmiştir. En güvenilir kemik yapıları sırasıyla omur, otolit, pul, ve operculum olarak tespit edilmiştir. Omur okumalarında en yüksek tutarlılık gözlendi (% 70.42). Bu çalışmada Carassius carassius da yaş I ve IX yaşları arasında değişmiştir.

In this study, it was aimed to make a comparative age determination in the population of Carassius carassius (Linne, 1758) living in Duhok River. For this purpose, 71 fish samples (57 male and 14 female) were obtained. The study was conducted in the fish anatomy laboratory of the Fisheries Faculty of Firat University. The length and weight of the fish samples were determined. The bony structures of the vertebrae, scales, otoliths, otoliths, and operculums used in the age determination were removed, cleaned and labeled. Then, bony structures were examined under binocular microscope. The age rings of each bony structure were counted three times and one day apart. The age groups determined for each bony structure, the number and percentage distributions of individuals in these groups were expressed with tables, and the comparison of age matching between bony structures was expressed by figures and the most reliable bony structures were vertebra, otolith, scales and operculum respectively.The highest consistency was observed in the vertebrae (70.42%). The ages changed between I and IX age in Carassius carassius in this study.
Duhok nehrinde (Irak) yaşayan Carassius carassius (Linne, 1758) yaş tespitinde en güvenilir kemiksi yapının belirlenmesi
Keywords: Su Ürünleri